THE IMPORTANCE OF EMPIRICAL CONCEPTS AND METHODS OF THEIR FORMATION - M. Tirkashov (American Journals, 2024)
The article examines the implementation of mental activity in the course of empirical cognition, collecting information about an object and making preliminary generalizations, creating a general description of an object, collecting data based on observations, systematizing and classifying data.
Keywords: Empirical knowledge, scientific knowledge, empirical concepts, empiricism, observation, experiment, comparison, measurement.